Infantile perianal pyramidal protrusion: a case report with dermoscopy and ultrasound findings - Arianna Lamberti; Georgios Filippou; Antonella Adinolfi; Michele Fimiani; Pietro Rubegni (Mattioli1885, 2015)
Infantile perianal pyramidal protrusion, it is a rare benign cutaneous condition described in relatively recent times. It is considered to be under-reported in the pediatric literature because it is often mistaken for other conditions. The unawareness of this lesion may be responsible for an excessive concern both in physician and in parents, which leads to overly aggressive and unnecessary treatments. Thus its recognition has many implications regarding proper management and treatment. We report a typical presentation of IPPP in which the diagnosis was based on the use of non-invasive diagnostic tools and in particular of dermoscopy and ultrasonography